Tuberculosis contact investigation in an intermediate burden setting: implications from a large tuberculosis contact cohort in Taiwan. Issue 2 (24th August 2017) - Lee, Meng-Rui; Ho, Cheng-Maw; Lee, Chih-Hsin; Lee, Ming-Chia; Chang, Lih-Yu; Yu, Kai-Lun; Ko, Jen-Chung; Wang, Jann-Yuan; Wang, Jann-Tay; Lee, Li-Na
There are still several unanswered research questions regarding tuberculosis (TB) contact investigations [1–4]. For example, up-to-date epidemiological studies regarding TB contacts in the area of intermediate incidence are not readily available [5]. The long-term risk of TB, especially beyond 5 years, remains undetermined [6]. Risk factors for TB development among contacts are also not well defined [2]. To expand current understanding and knowledge of TB contact investigation, we recruited a population-based TB contacts cohort utilising the National Health Insurance Research Database of Taiwan, which included medical care claims data of 99% Taiwan residents [7]. Taiwan TB contact cohort: 0.5% 1-year yield, age ≥65 as significant risk factor and elevated TB risk at 5th year http://ow.ly/9ZGr30dpkMc